2020
DOI: 10.1002/ange.202009278
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Lability Modulated by a Valence Electron Moving in and out of 25‐Atom Gold Nanoclusters

Abstract: The emergence of atomically precise metal nanoclusters with unique electronic structures provides access to currently inaccessible catalytic challenges at the single‐electron level. We investigate the catalytic behavior of gold Au25(SR)18 nanoclusters by monitoring an incoming and outgoing free valence electron of Au 6s1. Distinct performances are revealed: Au25(SR)18− is generated upon donation of an electron to neutral Au25(SR)180 and this is associated with a loss in reactivity, whereas Au25(SR)18+ is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…[12] In addition, Zhu and co-workers proved that the catalytic properties of Au 25 clusters for the intramolecular hydroamination of alkyne basically depended on the valenceelectron states of the Au 6s orbital, where Au 25 0 could promote the dissociative adsorption of reactants for enhanced activity relative to Au 25 + and Au 25 À clusters. [13] Similarly, the decreased electron densities of Ni sites in Nibased catalysts were found to facilitate the HOR catalysis. [4,14] Particularly, in view of the fact that the bond strengths in metal hydrides and oxides are highly associated with the valence-electron configuration of metal atoms, [15,16] the potential relationship between the adsorption behaviors of hydrogen/hydroxyl species and the valence-electron arrangement of metal active sites deserves to be investigated.…”
mentioning
confidence: 97%
“…[12] In addition, Zhu and co-workers proved that the catalytic properties of Au 25 clusters for the intramolecular hydroamination of alkyne basically depended on the valenceelectron states of the Au 6s orbital, where Au 25 0 could promote the dissociative adsorption of reactants for enhanced activity relative to Au 25 + and Au 25 À clusters. [13] Similarly, the decreased electron densities of Ni sites in Nibased catalysts were found to facilitate the HOR catalysis. [4,14] Particularly, in view of the fact that the bond strengths in metal hydrides and oxides are highly associated with the valence-electron configuration of metal atoms, [15,16] the potential relationship between the adsorption behaviors of hydrogen/hydroxyl species and the valence-electron arrangement of metal active sites deserves to be investigated.…”
mentioning
confidence: 97%
“…Because both clusters have enough space for the adsorption of 4‐NP, the influence of steric effects is believed to be minor in terms of the calculation of Gibbs free energy, which suggests that it is mainly affected by the electronic structures. These results indicate that 4‐NP is more easily adsorbed on 2 , which accounts for the superior activity of 2 [37, 46] . This study demonstrates that the electronic structure of a metal nanocluster can be modulated via the combination of ligands, and the catalytic performance can thus be improved.…”
Section: Resultsmentioning
confidence: 70%
“…For example, Zhu et al. reported that the stable 8‐electron [Au 25 (SCH 2 CH 2 Ph) 18 ] − showed lower catalytic activity than the unstable 7‐electron Au 25 (SCH 2 CH 2 Ph) 18 in the intramolecular hydroamination of 2‐ethynylaniline [37] . Therefore, the balance between stability and activity of cluster catalysts should be taken into consideration in terms of pursuing high catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to convoluted behaviors between surface and inside atoms of conventional heterogeneous catalysts, the clusters provide possible to study only one factor contribution to overall performances using unique pairs of clusters that possess the same surface with different cores or the same core with different surfaces [26, 27] . On the other hand, ligand‐protected metal clusters have been explored as homogeneous catalysts, where they keep advantages such as defined metal centre for creating reactive sites and surface ligands for orienting reactants and controlling selectivity, as well as overcome such minuses as separation from reaction systems and further boost their reutilization [28–30] . Obviously, these metal clusters provide opportunities to solve intrinsic issues related to homogeneous and heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%